UPAYA PENGEMBANGAN USAHA AGROINDUSTRI KAKAO MELALUI STRATEGI BISNIS DI KABUPATEN LOMBOK UTARA - Utama FR, Aeko Fria; Asasandi, I GN Aryawan (Fakultas Pertanian Universitas Mataram, 2025)
This study aims to identify and describe internal and external factors that influence strengths, weaknesses, opportunities, and threats, as well as to determine the right strategy in developing the cocoa agro-industry business in North Lombok Regency. The study was conducted in Genggelang Village, Gangga District, which was selected intentionally (purposive sampling) as the research location. Data collection was carried out through a survey method using a questionnaire and direct interviews with respondents. The data analysis technique used in this study was a SWOT analysis. The results of the study showed that the most appropriate strategy to implement was an aggressive strategy. This strategy includes optimizing the production process and improving product quality, which is carried out by utilizing raw materials efficiently, using skilled labor, and modern equipment and machinery. In addition, developing product variations while maintaining quality is also part of this strategy. Strengthening the marketing network is also needed to expand market reach and increase product visibility among consumers. This effort is carried out through promotions on various marketing platforms, participation in training, seminars, and exhibitions. In addition, regular evaluation of consumer input is very important to improve product deficiencies and increase competitiveness in the market.